Electromagnetic profiling and resistivity soundings in groundwater investigation near Egbeda- kabba, Kwara state (1990)
As part of a borehole siting programme for rural water supply in a Precambrian crystalline basement terrain, 36 Offset - Wenner electrical soundings and about 4.5 line-kilometres of ground conductivity profiling with a Gconics EM34-3 equipment were made near Egbeda-Kabba. Kwara Slate, Nigeria. The EM34-3 measurements provided a rapid reconnaissance tool in identifying high conductivity anomalies thought to be due to deep weathering and/or bedrock fissuring. The apparent conductivities arc generally less than 50 mmho m'1. A quantitative interpretation of the vertical sounding data indicated that the resistivity of the weathered zone varies over a wide range, from about 10 to 200 ohm.m, and that the overburden is generally less than 40m thick. Three abstraction wells, each having a yield of about 11s"1, were drilled at deeply weathered sites (depth to bedrock > 20m) identified from the surface geophysical measurements.